Analisis Risiko Kegagalan Proses Produksi Dodol Menggunakan Metode FTA, FMEA dan AHP - Hilmi Aulawi; Wahyu Andriyas Kurniawan; Sopian Sopian (Jurnal Kalibrasi, 2022)
Quality control in reducing production process failures is very important for every company. Because the smaller the production failure, the smaller the company's losses. The problems that occur in PD. Aditya Dodol is the number of production failures that occur every month, from 2-3% per month. This study aims to reduce or control the failure of the dodol production process using the Fault Tree Analysis (FTA) method to identify the factors that cause failure and the Failure Mode and Effect Analysis (FMEA) method to calculate the weight of each failure and the Analytical Hierarchy Process (AHP) method to formulate the company's alternative strategy to overcome the failure of the production process. The research results obtained that the failure of the production process is dominated by imperfect processing of raw materials, improper packaging processes and poor delivery processes. While the weight of the causes of failure of each process is caused by the number of employees who make mistakes and the strategy that must be carried out by the company is to provide opportunities for employees to convey ideas or ideas to the company.